EFFICACY OF DIFFERENT FUNGICIDES, BIOCIDES AND BOTANICAL EXTRACT SEED TREATMENT FOR CONTROLLING SEED-BORNE COLLETOTRICHUM SP. IN CHILLI (CAPSICUM ANNUUM L.) - C. S. CHOUDHARY,; S. C. JAIN,; RITESH KUMAR,; JAIPAL SINGH CHOUDHARY, (The Bioscan, 2013)
Chilli anthracnose caused by Colletotrichum capsici (Sydow) Butler and Bisby is one of the major constrain in the production of chilli in tropical and sub-tropical regions. Present research was aimed at studying the efficacy of various chemical and biocidal agents on the germination and seedling vigour of C. capsici infected chilli seeds. Among different seed treatments, Safeda leaves extract, Neem seed extract, tulsi leaves extract, Thiram, Captan and Bavistin were found superior and significantly higher seed germination as compared to other treatments and control. Among different bioagents used for the experiment, maximum per cent seed germination (82.35%) was recorded in seed treated with T. viride. Pre and post emergence mortality was minimum in case of T. polysporum (2.65% and 6.10%) followed by T. viride (6.00% and 6.80%). Bavistin was most effective with 93.00% (68.00% in control) seed germination with no pre or post emergence mortality and increased seedling vigour index of 506.85 which was 306.00 in control. Maximum per cent seed germination and seedling vigour index was observed in seed treated with leaf extract of E. tereticornis with germination percent of 94.00 and seedling vigour index of 540.05. Among all treatments maximum root/shoot length and vigour index was found by T. viride, Safeda, Bavistin and Thiram treated seeds and found superior to others.